Biodegradable and transparent cellulose film prepared eco-friendly from durian rind for packaging application. (September 2019) - Zhao, Guili; Lyu, Xiaomei; Lee, Jaslyn; Cui, Xi; Chen, Wei-Ning
Highlights: Cellulose with high purity was obtained from durian rind to make transparent film. The cellulose film with good appearance was successfully prepared from durian rind. The cellulose film obtained had good mechanical property and high biodegradability. This work shows a potential application of durian rind in biodegradable packaging. Abstract: High purity cellulose was isolated from durian rind in this study. Cellulose films were successfully regenerated from cellulose solution in lithium chloride/N, Ndimethylacetamide using water as regeneration solvent. The X-ray diffraction and FTIR results revealed that the durian-rind cellulose (DC) fiber was similar to commercial cellulose derived from cotton linters. The regenerated cellulose film exhibited good appearance with smooth surface and excellent transparency. The tensile tests results showed that DC film possessed high rigidity and tensile strength. The biodegradation analysis indicated that DC film could be 100% broken down in soil in 4 weeks, higher biodegradation percentage than that of cellophane, suggesting outstanding biodegradability of DC film. This work provides a potential application of conversion of durian rind as well as other cellulosic waste resource into biodegradable packaging and other functional materials.